ESO889468 Supplementary material - Supplemental material for Effect of haemoglobin levels on outcome in intravenous thrombolysis-treated stroke patients ... - Altersberger, Valerian L; Kellert, Lars; Abdulaziz S Al Sultan; Martinez-Majander, Nicolas; Hametner, Christian; Eskandari, Ashraf; Heldner, Mirjam R; Berg, Sophie A Van Den; Zini, Andrea; Visnja Padjen; Kägi, Georg; Pezzini, Alessandro; et al. (SAGE Journals, 2019)
Supplemental material, ESO889468 Supplementary material for Effect of haemoglobin levels on outcome in intravenous thrombolysis-treated stroke patients by Valerian L Altersberger, Lars Kellert, Abdulaziz S Al Sultan, Nicolas Martinez-Majander, Christian Hametner, Ashraf Eskandari, Mirjam R Heldner, Sophie A van den Berg, Andrea Zini, Visnja Padjen, Georg Kägi, Alessandro Pezzini, Alexandros Polymeris, Gian M DeMarchis, Marjaana Tiainen, Silja Räty, Stefania Nannoni, Simon Jung, Thomas P Zonneveld, Stefania Maffei, Leo Bonati, Philippe Lyrer, Gerli Sibolt, Peter A Ringleb, Marcel Arnold, Patrik Michel, Sami Curtze, Paul J Nederkoorn, Stefan T Engelter, Henrik Gensicke and for the Thrombolysis in Stroke Patients (TRISP) collaborators in European Stroke Journal ...